Odraz interkulturních vztahů v srbské a rumunské frazeologiiReflection of Intercultural Relations in Serbian and Romanian Phraseology - Krucká, Barbora (Studia mythologica Slavica, 2014)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This research examines the reflection of intercultural relations of Serbian and Romanian speech community members in their phraseology. It also focuses at the auto-stereotypes and hetero-stereotypes present in phraseology. As a shared collective experience imposed in the language, phraseology also entails the summary of judgments about the world of a particular speech community, and thus its relationship to its own culture, as well as to different cultures. Proverbs and phrases from the collections of proverbs form a corpus, which is quantitatively analysed. This results in a view of perception of their own nation and ethnical, national and religious groups members in prolonged contact with Serbian and Romanian speech community.